Factors Associated With Job Satisfaction in Medical Oncology Practices: Results From a Multisite Survey. (April 2021) - Friese, Christopher R.; Mendelsohn-Victor, Kari; Medvec, Barbara R.; Ghosh, Bidisha; Bedard, Louise; Griggs, Jennifer J.; Manojlovich, Milisa
Abstract : OBJECTIVE: The aim of this study was to examine the factors influencing job satisfaction of nurses, physicians, and advanced practice providers in ambulatory oncology settings. BACKGROUND: Job satisfaction is essential to clinician well-being and quality of care. METHODS: In 2017, clinicians from 29 ambulatory medical oncology practices completed anonymous paper questionnaires that examined job satisfaction, clinician-to-clinician communication, and perceptions of patient safety. Linear regression, adjusted for clustered observations, examined the relationship between job satisfaction, clinician communication, and patient safety perceptions. RESULTS: Of 280 respondents (response rate of 68%), 85% reported that they were satisfied or very satisfied with their current position. Patient safety and accuracy of clinician communication were positively and significantly associated with job satisfaction. CONCLUSIONS: Although most surveyed clinicians were satisfied, 15% were dissatisfied and reported communication and safety concerns. Leadership efforts to strengthen clinician communication actions and develop positive safety cultures are promising strategies to promote clinician well-being and high-quality cancer care.